2018
DOI: 10.4274/atfm.66375
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment in Non-Small Cell Lung Cancer

Abstract: Lung cancer occurred in approximately 1,8 million patients and caused an estimated 1,6 million deaths in 2012, worldwide. NSCLC constitutes approximately 85% of all lung cancers. Patients with early-stage NSCLC are surgically treated for curative goals. However, many patients are at risk of recurrence despite complete resection. This suggests that a large proportion of patients have the micrometastatic disease even at the early course of the disease. In this review, we aimed to evaluate the results of adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In some of the cases that have a chance for surgical treatment, postoperative anticancer treatment methods (chemotherapy, radiotherapy, immunotherapy, or combinations) may be given according to the histopathological examination results of the surgical material and stage of the disease. Many studies have reported that anticancer treatments, especially chemotherapy treatment, have a positive effect on survival and reduce the risk of distant metastasis and local recurrence [ 3 , 5 7 , 11 ]. Despite these positive effects of chemotherapy, there are many adverse effects such as nausea, vomiting, diarrhea, other gastrointestinal system side effects, anorexia, malabsorption, weight loss, anemia, fatigue, electrolyte imbalance, cognitive disorders, neurotoxicity, nephrotoxicity, neutropenia, and increased risk of sepsis [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some of the cases that have a chance for surgical treatment, postoperative anticancer treatment methods (chemotherapy, radiotherapy, immunotherapy, or combinations) may be given according to the histopathological examination results of the surgical material and stage of the disease. Many studies have reported that anticancer treatments, especially chemotherapy treatment, have a positive effect on survival and reduce the risk of distant metastasis and local recurrence [ 3 , 5 7 , 11 ]. Despite these positive effects of chemotherapy, there are many adverse effects such as nausea, vomiting, diarrhea, other gastrointestinal system side effects, anorexia, malabsorption, weight loss, anemia, fatigue, electrolyte imbalance, cognitive disorders, neurotoxicity, nephrotoxicity, neutropenia, and increased risk of sepsis [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients scheduled for postoperative chemotherapy must endure all the challenges of postoperative recovery as well as the adverse effects of chemotherapy, in addition to the presenting symptoms of the existing malignancy. The increased metabolic requirements following anatomic pulmonary resection become even more apparent under the catabolic effects of chemotherapy, and this process is also adversely affected by several factors, such as pain, anxiety, impaired taste, and loss of appetite, resulting in a considerable reduction in food intake [ 3 , 10 , 14 ]. This issue has also inspired various studies, and it has been shown that in patients with lung cancer, 30 to 73% of the patients have malnutrition and weight loss despite various treatment methods [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung cancers can be divided into two main groups: small cell lung cancer (SCLC) and non–small cell lung cancer (NSCLC), of which the latter accounts for approximately 85% of all lung cancers. 2 Treatment decisions for lung cancers are based mainly on patient-specific characteristics, such as tumor histology, disease stage, age, pulmonary functions, and comorbidities. 3 Surgery is the most effective treatment of choice for early-stage NSCLC, 4 5 and is believed to be associated with differences in postoperative complications, recurrence, metastasis, and survival, depending on the choice of surgical procedure.…”
Section: Introductionmentioning
confidence: 99%